Speciation of Pd(OAc)2 in Ligandless Suzuki-Miyaura Reaction - Nguyen,BN; Adrio,LA; Guilera,G; Livingston,AG; Hii,KKM (Catalysis Science & Technology, 2011)
Generation of catalytically active Pd(0) species from Pd(OAc)2 has been examined, in the context of Suzuki–Miyaura reactions involving substitution of aryl bromides under aerobic and ambient conditions. Using a combination of spectroscopic, microscopic and kinetic measurements, the role of each reaction component is delineated in the speciation of the palladium species. Among the key findings are the effects of O2, H2O and inorganic base, and implications for catalytic activity.